Influence of Gender on Cardiac and Encephalic Inflammation in the Elderly with Cysticercosis: A Case Control Study - Camila Lourencini Cavellani; Rosana Rosa Miranda Corrêa; Mara Lúcia Fonseca Ferraz; Laura Penna Rocha; Ana Carolina Guimarães Faleiros; Ruy de Souza Lino Junior; Marlene Antônia dos Reis; Vicente de Paula Antunes Teixeira (Journal of Tropical Medicine)
Background. The present study explores the influence of the host’s age and gender upon the inflammatory infiltrate. We aimed to quantify the inflammatory infiltrate caused by cysticercosis, which is related to aging, in the heart and in the encephalon. Methods. 75 autopsy protocols with cysticercosis diagnosis from department of pathology at a university hospital from 1970 to 2008 were reviewed. Two groups were formed: elderly with cysticercosis and nonelderly with cysticercosis. We used KS-300 (Kontron-Zeiss) software for morphometric analysis of the inflammation. Results. The elderly had an average of 3.1±2.5 cysticerci, whereas the non-elderly had 2.7±3.8 parasites. The non-elderly group with cysticercosis had significantly more inflammation, both cardiac and encephalic, than the elderly group. The elderly females with cysticercosis had more cardiac and encephalic inflammation. Conclusions. In this study, we showed that the non-elderly had significantly more cardiac and encephalic inflammation than the elderly, and that such inflammatory infiltrate decreases with age and depends upon the evolutionary stage of the cysticercus. Furthermore, there are differences concerning gender in the intensity of the inflammatory response due to cysticerci in the heart and brain parenchyma during senescence. Even during this period, women continue to have a more intense response to the parasitosis.